THE EFFECT OF BRAND AWARENESS AND PERCEIVED QUALITY ON CUSTOMER SATISFACTION OF STARBUCKS COFFEE IN MALANG - Ramadhan, Riandi (Jurnal Ilmiah Mahasiswa FEB, 2017)
The purpose of this research is to examine the influence of Brand Awareness and Perceived Quality on Customer Satisfaction of Starbucks Coffee in Malang. In order to know the relationship among Brand Awareness and Perceived Quality towards Customer Satisfaction, a regression analysis, F-test, T-test, was applied. The samples in this research is 150 customers of Starbucks Coffee in Malang as the respondents to collect the data. The sampling technique was a purposive sampling with 150 respondents and the research instrument employed demographic background, Brand Awareness, Perceived Quality and Customer Satisfaction.The test is using validity test, reability test, and classical assumption test. The hypothesis testing was using F and T test to analyze the data to be used in Multiple Regression Analysis. The result showed that Brand Awareness and Perceived Quality influence Customer Satisfactionsignificantly to Starbucks Coffee in Malang both partially and simultaneously. Therefore, Perceived Quality is the dominant factor in creating Customer Satisfaction.Â Keywords :Brand Awareness, Perceived Quality, Customer Satisfaction.